Antibacterial Activity of Mouthwash with Celery and Cinnamon Extracts Against Streptococcus mutans and Staphylococcus aureus - Agung Nur Cahyanta; Dian Rahmawati; Prihastini Setyo Wulandari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Dental caries remains a major oral health problem in Indonesia and is closely associated with dental plaque accumulation caused by pathogenic bacteria such as Streptococcus mutans and Staphylococcus aureus. The prolonged use of chemical mouthwashes may cause undesirable side effects, encouraging the development of safer herbal alternatives. Celery (Apium graveolens) and cinnamon (Cinnamomum burmanni) contain flavonoids, phenolics, and essential oils with antibacterial activity. This study aimed to evaluate the physical properties, antibacterial activity, and optimal combination ratio of celery and cinnamon extracts in mouthwash formulations. Ethanol extracts obtained by maceration were formulated into three formulations, F1 (5%:10%), F2 (7.5%:7.5%), and F3 (10%:5%). Physical evaluations included organoleptic properties, pH, homogeneity, and viscosity tests. Antibacterial activity was evaluated using the disc diffusion method and analyzed using one-way ANOVA and multiple linear regression. All formulations met the required physical evaluation criteria. F1 exhibited the highest antibacterial activity, with inhibition zones of 15.17 mm against S. mutans and 18.29 mm against S. aureus. Regression analysis revealed that cinnamon extract was the dominant factor, while statistical analysis showed significant differences among formulations (p < 0.05). In conclusion, F1 was identified as the optimal mouthwash formulation.